Adult cancer patients satisfaction of nursing care: a cross-national evaluation of two Southeastern European countries - Charalambous, Andreas; Efstathiou, Georgios; Adamakidou, Theodoula; Tsangari, Haritini (My University, 2014)
Objective: To assess and compare the perceived patient satisfaction with the nursing care in two European countries. Methods: This was a multicenter cross-national descriptive study. The study included various centers both specialized and general that provide cancer care. The data were collected from hospitalized cancer patients in Greece and Cyprus with the Greek version of the Risser Patient Satisfaction Scale. The scale assessed patients' satisfaction on three distinct dimensions namely "Technical-professional", "Interpersonal-educational" and "Interpersonal-trusting". Results: The analyses revealed that there are significant differences in the total scale (p<0.05) and the interpersonal-trusting subscale (p<0.001) between the two countries. In order to gain an in-depth understanding of these findings, the qualitative analysis revealed that the following main themes contributed to the way the patients experienced their hospitalisation: 'safety', 'fear', 'lack of information' and 'continuity of the care'. The patients attributed increased importance to the interpersonal-trusting aspects' influence on their satisfaction. Based on the qualitative data, this was attributed to two main themes namely 'individuality' and 'humane care'. Conclusions: The European environment offers an ideal setting to examine satisfaction variations among patients. Although the findings demonstrated a positively skewed attitude by the patients towards the care provided by the nurses in both countries, these findings also revealed significant differences. The patients' experiences were explored in light of variations in culture, health systems and the actual differences in quality as perceived by patients.
Keywords: Adult cancer patients; Health research; Health system; Nursing care; Patient satisfaction